2008
DOI: 10.1097/cco.0b013e32830b0dc2
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preserving surgery for carcinoma of the cervix

Abstract: Radical vaginal trachelectomy appears safe when performed in centres with appropriate experience of radical vaginal surgery and laparoscopic techniques. The impact of this new approach questions traditional teaching, thus preserving potential fertility in up until now impossible circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 18 publications
1
34
0
2
Order By: Relevance
“…Those results suggested that the management after radical trachelectomy, including high risk pregnancy, is important. The criteria for performing radical trachelectomy have been reported by several authors [3][4][5][6]. The suggested criteria were, in principle, as follows: ''A desire for future fertility'', ''FIGO stage Ia1 with lymphovascular invasion, stage Ia2, or Ib1'', ''Tumor size B2 cm'', ''Tumor limited to the cervix'', and ''No evidence of pelvic lymph node metastasis and/or other distant metastasis''.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those results suggested that the management after radical trachelectomy, including high risk pregnancy, is important. The criteria for performing radical trachelectomy have been reported by several authors [3][4][5][6]. The suggested criteria were, in principle, as follows: ''A desire for future fertility'', ''FIGO stage Ia1 with lymphovascular invasion, stage Ia2, or Ib1'', ''Tumor size B2 cm'', ''Tumor limited to the cervix'', and ''No evidence of pelvic lymph node metastasis and/or other distant metastasis''.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports on radical trachelectomy [5][6][7][8]; however, its status is not clear in Japan. We therefore conducted a questionnaire survey to clarify the current status of radical trachelectomy in Japan.…”
Section: Introductionmentioning
confidence: 96%
“…However, the use of radical trachelectomy (excision of the cervix and parametria only) with lymph node dissection has been proposed as a fertility-sparing technique in young women who wish to retain their fertility [4]. Trachelectomy 0022-3468/$ -see front matter…”
Section: Wwwelseviercom/locate/jpedsurgmentioning
confidence: 99%
“…Bis 2008 wurde bei mehr als 900 durchgeführten Trachelektomie über mehr als 300 Schwangerschaften mit 196 Lebendgeburten berichtet [26]. Aktuelle Veröf-fentlichungen versuchen, auf Basis bislang veröffentlichter Studien, die nicht primär prospektiv die Schwangerschaftsverläufe zum Gegenstand hatten, Empfehlungen zur Schwangerschaftsbetreuung nach einer Trachelektomie zu geben [34].…”
Section: Schwangerschaftsverläufeunclassified